Evaluation of effective factors on theoretical classes’ attendance of dentistry students of Babol University of Medical Sciences - Maryam Seyedmajidi (Babol University of Medical Sciences, 2017)
BACKGROUND AND OBJECTIVE: The characters and roles of teachers and demographic characteristics and attendance of students have special places in classroom. Students are interested to participate in classroom logically and manner of faculty members’ teaching manner determine students' attendance in class. This study aimed to investigate the factors influencing the students' attendance in theoretical classes from the perspective of dental students of Babol Dentistry School.